Theological Ethics and Healthcare Justice: Addressing Disparities in Indonesia’s Health System (Indonesian Theological Justice Review, 2024)
Indonesia’s healthcare system faces significant challenges in providing equitable access to medical services, particularly for marginalized and rural populations. This paper explores the theological ethics of healthcare justice, examining how religious perspectives can inform and address disparities within the Indonesian health system. Drawing on Islamic and Christian teachings, the study evaluates how religious principles such as justice, charity, and compassion can inform healthcare policies and practices. Islamic concepts of social justice, such as the duty to care for the sick and the concept of health as a divine trust, are compared with Christian values of healing and compassion for the vulnerable. The research examines case studies of faith-based hospitals, clinics, and healthcare initiatives in Indonesia, assessing their effectiveness in bridging gaps in healthcare access. The paper argues that while theological ethics can provide a moral foundation for addressing health disparities, challenges remain in translating these principles into systemic reforms. Recommendations include integrating theological ethics into healthcare education, fostering partnerships between religious institutions and the government, and advocating for policies that ensure equitable healthcare for all Indonesians.